National Development Plan as an Entrepreneurial Mechanism for Rural Economic Development in South Africa - Elvin Shava; Tafadzwa Clementine Maramura (Journal of Economics and Behavioral Studies, 2017)
Chapter 6 of the National Development Plan (NDP) accentuates on the impact of an integrated and inclusive rural economy by proposing for the creation 643 000 direct jobs and 326 000 indirect jobs in the farming and non-farming sector by 2030. Discussion within the study reveals that, the NDP was also designed to stimulate rural economic development among other important dynamic economic factors of the country. However, five years into the implementation of the NDP, remnants of inequality, unemployment and poverty are still apparent amongst the rural population. This paper indicates that the success of NDP as an entrepreneurial mechanism is being underpinned by contestations which are emanating from under-financing, lack of entrepreneurial education and research culture, negative attitudes of the people, corruption and red tape. Through a qualitative research approach, the paper observes that, for NDP to be continuously coordinated as an economic initiative, financing of rural projects such as small businesses, cooperatives and other rural development projects should be the government’s key priority. The study concludes that entrepreneurship has to be considered as a prime mover in rural economic development in South Africa since an entrepreneurial economy significantly differs from a non-entrepreneurial one, as evidenced by the economic vigour and sustainable development of its inhabitants.